DEVELOPMENT OF AESTHETIC FEELINGS OF FUTURE TEACHERS TECHNOLOGIES (Pedagogy of Higher and Secondary Education, 2008)
In this article і analyse the importance of developing of esthetic feelings. The meaning of developing of esthetic feeling for the social activity of future teacher is opening.